Cognition as Free Activity (II) - Lozuraitis, Albinas (Problemos, 1973)
The present part of the paper (see also Problemos, Nr. 9, 1972) considers the methodological principles of the Marxist philosophy in solving the gnoseological problem. Treating cognition as creative activity (Hegel’s view) and recognition of the sensual reality of the world (the view of the French materialists) are regarded as prerequisites for the solution of the above problem. The combination of the two prerequisites was made possible due to the new approach to the interrelation between theory and experience. Marx began treating the human activity as an objective one and reality as an experience. The process of changes in nature and in creating the world of culture is the basis of free purposeful activity of man, the theoretical assimilation of reality constituting a peculiar aspect of this activity. Thus the principle of freedom is applicable to the definition of cognition and the results thereof.